Pregunta
upstudy study bank question image url

1. ABCDEF is a regular hexagon in which \( \overrightarrow{B C} \) rep- resents \( \underline{b} \) and \( \overrightarrow{F C} \) represents \( 2 \underline{a} \). Express the vectors \( \overrightarrow{A B}, \overrightarrow{C D} \) and \( \overrightarrow{B E} \) in terms of \( \underline{a} \) and \( \underline{b} \).

Ask by Malone Allan. in the United Kingdom
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

\( \overrightarrow{A B} = \underline{a} \), \( \overrightarrow{C D} = -\underline{a} \), and \( \overrightarrow{B E} = -2\underline{a} \).

Solución

To express the vectors \( \overrightarrow{A B}, \overrightarrow{C D} \), and \( \overrightarrow{B E} \) in terms of \( \underline{a} \) and \( \underline{b} \), we first need to understand the geometry of the regular hexagon ABCDEF. 1. **Understanding the Hexagon:** - A regular hexagon can be inscribed in a circle, and each vertex can be represented in terms of complex numbers or vectors in a coordinate system. - The vertices can be labeled as follows: - \( A \) at \( (1, 0) \) - \( B \) at \( \left(\frac{1}{2}, \frac{\sqrt{3}}{2}\right) \) - \( C \) at \( \left(-\frac{1}{2}, \frac{\sqrt{3}}{2}\right) \) - \( D \) at \( (-1, 0) \) - \( E \) at \( \left(-\frac{1}{2}, -\frac{\sqrt{3}}{2}\right) \) - \( F \) at \( \left(\frac{1}{2}, -\frac{\sqrt{3}}{2}\right) \) 2. **Given Vectors:** - \( \overrightarrow{B C} = \underline{b} \) - \( \overrightarrow{F C} = 2 \underline{a} \) 3. **Calculating the Vectors:** - The vector \( \overrightarrow{B C} \) can be calculated as: \[ \overrightarrow{B C} = \overrightarrow{C} - \overrightarrow{B} = \left(-\frac{1}{2}, \frac{\sqrt{3}}{2}\right) - \left(\frac{1}{2}, \frac{\sqrt{3}}{2}\right) = (-1, 0) \] - Therefore, we have: \[ \underline{b} = (-1, 0) \] - The vector \( \overrightarrow{F C} \) can be calculated as: \[ \overrightarrow{F C} = \overrightarrow{C} - \overrightarrow{F} = \left(-\frac{1}{2}, \frac{\sqrt{3}}{2}\right) - \left(\frac{1}{2}, -\frac{\sqrt{3}}{2}\right) = (-1, \sqrt{3}) \] - Therefore, we have: \[ 2 \underline{a} = (-1, \sqrt{3}) \implies \underline{a} = \left(-\frac{1}{2}, \frac{\sqrt{3}}{2}\right) \] 4. **Expressing Other Vectors:** - Now we can express the required vectors: - **For \( \overrightarrow{A B} \):** \[ \overrightarrow{A B} = \overrightarrow{B} - \overrightarrow{A} = \left(\frac{1}{2}, \frac{\sqrt{3}}{2}\right) - (1, 0) = \left(-\frac{1}{2}, \frac{\sqrt{3}}{2}\right) = \underline{a} \] - **For \( \overrightarrow{C D} \):** \[ \overrightarrow{C D} = \overrightarrow{D} - \overrightarrow{C} = (-1, 0) - \left(-\frac{1}{2}, \frac{\sqrt{3}}{2}\right) = \left(-\frac{1}{2}, -\frac{\sqrt{3}}{2}\right) = -\underline{a} \] - **For \( \overrightarrow{B E} \):** \[ \overrightarrow{B E} = \overrightarrow{E} - \overrightarrow{B} = \left(-\frac{1}{2}, -\frac{\sqrt{3}}{2}\right) - \left(\frac{1}{2}, \frac{\sqrt{3}}{2}\right) = (-1, -\sqrt{3}) = -2\underline{a} \] 5. **Final Expressions:** - Thus, we have: - \( \overrightarrow{A B} = \underline{a} \) - \( \overrightarrow{C D} = -\underline{a} \) - \( \overrightarrow{B E} = -2\underline{a} \) In summary: - \( \overrightarrow{A B} = \underline{a} \) - \( \overrightarrow{C D} = -\underline{a} \) - \( \overrightarrow{B E} = -2\underline{a} \)

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Bonus Knowledge

To express the vectors \( \overrightarrow{A B}, \overrightarrow{C D}, \) and \( \overrightarrow{B E} \) in terms of \( \underline{a} \) and \( \underline{b} \), we start by using the given data about the hexagon ABCDEF. 1. The vector \( \overrightarrow{A B} \) can be determined by recognizing \( A \) is positioned at an angle \( 60^\circ \) counterclockwise from \( B \). Thus, \( \overrightarrow{A B} = \overrightarrow{B C} + \overrightarrow{C A} = \underline{b} + (-\frac{1}{2}\underline{b} + \frac{\sqrt{3}}{2}\underline{a}) = \frac{1}{2} \underline{b} + \frac{\sqrt{3}}{2} \underline{a} \). 2. For \( \overrightarrow{C D} \), since \( C \) and \( D \) are consecutive vertices of the hexagon, we know \( C \) is moving \( 60^\circ \) counterclockwise to reach \( D \). Hence, \( \overrightarrow{C D} = \frac{1}{2} \underline{b} - \frac{\sqrt{3}}{2} \underline{a} - \overrightarrow{B C} = \frac{1}{2}\underline{b} - \underline{b} = -\frac{1}{2} \underline{b} + \frac{\sqrt{3}}{2} \underline{a} \). 3. Lastly, for \( \overrightarrow{B E} \), we can note that moving from \( B \) to \( E \) means traversing half the perimeter of the hexagon. So, \( \overrightarrow{B E} = \overrightarrow{B C} + \overrightarrow{C D} + \overrightarrow{D E} = \underline{b} - \frac{1}{2} \underline{b} + \underline{b} = \frac{3}{2} \underline{b} - \underline{a} \). So, - \( \overrightarrow{A B} = \frac{1}{2} \underline{b} + \frac{\sqrt{3}}{2} \underline{a} \) - \( \overrightarrow{C D} = -\frac{1}{2} \underline{b} + \frac{\sqrt{3}}{2} \underline{a} \) - \( \overrightarrow{B E} = \frac{3}{2} \underline{b} - \underline{a} \)

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad